2010
DOI: 10.1111/j.1750-3639.2009.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Targets of Oxidative Damage in Human Neurodegenerative Diseases with Abnormal Protein Aggregates

Abstract: Human neurodegenerative diseases with abnormal protein aggregates are associated with aberrant post-translational modifications, solubility, aggregation and fibril formation of selected proteins which cannot be degraded by cytosolic proteases, ubiquitin-protesome system and autophagy, and, therefore, accumulate in cells and extracellular compartments as residual debris. In addition to the accumulation of "primary" proteins, several other mechanisms are involved in the degenerative process and probably may expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
173
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 129 publications
(250 reference statements)
4
173
0
1
Order By: Relevance
“…Moreover, some studies have demonstrated in detail which proteins are oxidatively damaged (110). Oxidized proteins detected in NDs can be divided into different functional groups: (i) glycolysis and energy metabolism, (ii) mitochondrial proteins, (iii) cytoskeleton, (iv) chaperones, and (v) members of the UPS.…”
Section: Protein Oxidation In Ndsmentioning
confidence: 99%
“…Moreover, some studies have demonstrated in detail which proteins are oxidatively damaged (110). Oxidized proteins detected in NDs can be divided into different functional groups: (i) glycolysis and energy metabolism, (ii) mitochondrial proteins, (iii) cytoskeleton, (iv) chaperones, and (v) members of the UPS.…”
Section: Protein Oxidation In Ndsmentioning
confidence: 99%
“…Exposure to oxidative stress can lead to oxidative protein damage that directly alters protein structure, leading to dramatic decreases in their activity and/or aggregation of partially denatured proteins. Aberrant protein aggregation in brain tissue is a key feature of the major neurodegenerative disorders associated with aging (Martinez et al 2008). To maintain protein function in the face of oxidative stress, cells utilize "protein repair" enzymes, capable of maintaining protein redox homeostasis through the regulation of thiol-disulfide exchange on critical residues, particularly cysteine.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Age-related macular degeneration (AMD) is a neurodegenerative disease of the eye and the leading cause of central blindness in western countries. 7,8 Currently, for 80% to 85% of the 30 to 50 million AMD patients worldwide there are no effective treatment alternatives.…”
Section: Introductionmentioning
confidence: 99%